Hedgehog is required for the proliferation and specification of ovarian somatic cells prior to egg chamber formation in Drosophila. - Forbes, A.J.; Lin, H.; Ingham, P.W.; Spradling, A.C. (Development, 1996)
The hedgehog (hh) gene plays a role in regulating cell proliferation and specifying cell identity in diverse systems. We show that hh is expressed at the extreme apical end of Drosophila ovarioles in terminal filament cells and a newly identified group of associated somatic cells. Reducing or ectopically expressing hh affects somatic cells in region 2 of the germarium, 2-5 cells away from the cells in which Hh protein is detected. hh activity stimulates the proliferation of pre-follicle somatic cells, and promotes the specification of polar follicle cells. hh signaling during egg chamber assembly appears to be closely related to, or part of pathways involving the neurogenic genes.